2015
DOI: 10.1159/000365352
|View full text |Cite
|
Sign up to set email alerts
|

Pleuropulmonary Blastoma in a Neonate Diagnosed Prenatally as Congenital Pulmonary Airway Malformation

Abstract: Pleuropulmonary blastoma is an extremely rare lung neoplasm exclusive to children under 5 years of age. It presents a diagnostic challenge both prenatally and in early childhood due to its similarity to benign lung cysts, which are managed differently. We present the first case, to our knowledge, of a neonate with pleuropulmonary blastoma and myelomeningocele, though prenatally diagnosed as a congenital pulmonary airway malformation. We detail the prenatal imaging that facilitated counseling and delivery manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
1
5
0
5
Order By: Relevance
“…Fetal congenital lung lesions (CLLs) are a heterogeneous group of lesions that most commonly include entities such as congenital pulmonary airway malformation (CPAM) and bronchopulmonary sequestration (BPS), less frequent entities such as congenital lobar emphysema and bronchial atresia, and some rare forms of embryonal tumors, including pleuropulmonary blastoma …”
mentioning
confidence: 99%
“…Fetal congenital lung lesions (CLLs) are a heterogeneous group of lesions that most commonly include entities such as congenital pulmonary airway malformation (CPAM) and bronchopulmonary sequestration (BPS), less frequent entities such as congenital lobar emphysema and bronchial atresia, and some rare forms of embryonal tumors, including pleuropulmonary blastoma …”
mentioning
confidence: 99%
“… 21 , 38 , 39 Less than 5% of PPBs are detected prenatally. 18 , 20 , 40 , 41 The only radiologic feature that is thought to be pathognomic for benign disease is the presence of a systemic feeding vessel, 16 , 18 and our study radiologists correctly excluded malignancy in their review of all confirmed BPS lesions. The significance of other image-based characteristics in identifying PPB is more controversial.…”
Section: Discussionmentioning
confidence: 66%
“…It does not appear that there is a relevant correlation between prenatal sonographic appearance of these lesions and the final histopathology diagnosis, which is illustrated well in the report by Coleman et al [1,2] . PPB is a rare embryonic tumor which should be included in the differential diagnosis of any fetal congenital lung lesion diagnosed prenatally.…”
Section: Disclosure Statementmentioning
confidence: 86%
“…The lesion was removed in the early neonatal period due to respiratory morbidity [1] . This report illustrates several important points pertinent to the management of prenatally diagnosed fetal congenital lung lesions.…”
Section: Disclosure Statementmentioning
confidence: 99%